1992
DOI: 10.1021/tx00028a014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling cyanide release from nitriles: prediction of cytochrome P 450-mediated acute nitrile toxicity

Abstract: A mechanism-based model for prediction of acute nitrile toxicity was developed using octanol-water partition coefficients (log P) and estimated rates of alpha-hydrogen atom abstraction as variables. Relative rates of hydrogen atom abstraction were derived from differences in heats of formation for ground-state and radical geometries and radical ionization potentials. Calculated energies of activation for all potential sites of oxidation for a given nitrile were used to estimate partitioning of metabolites amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The required diversity is accomplished by families and subfamilies of enzymes with generally broad substrate specificities, a very reactive oxygenating species and a broad regioselectivity. Thus, for many reactions, the electronic features of the substrate are all that are required to predict regioselectivity (Grogan et al, 1992;Harris et al, 1992;de Groot et al, 1995de Groot et al, , 1999Yin et al, 1995).…”
mentioning
confidence: 99%
“…The required diversity is accomplished by families and subfamilies of enzymes with generally broad substrate specificities, a very reactive oxygenating species and a broad regioselectivity. Thus, for many reactions, the electronic features of the substrate are all that are required to predict regioselectivity (Grogan et al, 1992;Harris et al, 1992;de Groot et al, 1995de Groot et al, , 1999Yin et al, 1995).…”
mentioning
confidence: 99%
“…Thus, this model depends only on ground-state energies to calculate activation energies. Previous studies on the relationship of activation energies for hydrogen-atom abstraction, calculated with this model, to the LD50 values of 26 nitriles (10) and to the amount of urinary trifluoroacetic acid formed from four H(C)FCs in rats (11) indicated that the PNR model may have the potential to predict rates of biotransformation by CYP. The present study was undertaken to test the capacity of the PNR model to predict rates of halogenated alkane biotransformation.…”
mentioning
confidence: 99%
“…For compounds that are directly biotransformed to toxic products-e.g., nitriles being converted to cyanide-biotransformation and toxicity are well correlated (10) neoantigen formation (23). For the inhalation anesthetics presented in this study, a correlation between rate of metabolism to give fluoride and renal toxicity also exists (20).…”
mentioning
confidence: 99%
“…Another example is the study on the neurotoxic effects of nitriles (compounds with a cyano, R-CN, group) on the sensory and central nervous systems. Many nitriles are known to cause acute toxicity through cyanide release by xenobiotic metabolism enzymes, a toxic endpoint already addressed by some modeling studies (Grogan et al, 1992). The work by several groups, including ours, has demonstrated that several nitriles cause a variety of neurotoxic effects, such as degeneration of specific populations of neurons in the central nervous system (Boadas-Vaello et al, 2005;Seoane et al, 2005) and degeneration of sensory systems including the olfactory (Genter et al, 1992), auditory (Gagnaire et al, 2001) and vestibular systems (Llorens et al, 1993;Llorens, 2001, 2003).…”
Section: Regulatory Neurotoxicity Testing For Risk Assessment Purposementioning
confidence: 99%